Obituaries: 4 (Knight-Ridder/Tribune Business News, 2008)
A memorial service was held 11 a.m. Wednesday, June 4, 2008, at Faith Lutheran Church in Hutchinson, with interment in the Oakland Cemetery. Ruth enjoyed spending time with her family and bird watching.